From Marx and Engels to Sino-Marxism Focusing on Communist and Confucian (rujia) Notions of Loyalty and Self-Criticism - Gregor Paul (Asian Studies, 2021)
The paper sketches and compares main components of Marxism, Leninism, Stalinism, and Sino-Marxism, especially Maoism. In particular, it deals with the relation between Maoism and so-called Confucianism (rujia). It is argued that this relation has been—and still is—characterized by both Maoist criticism of Confucius as well as absorption of ‘Confucian’ ideas. In briefly analysing commonalities and differences between the various theories and ‘practices’, especially the ways the Communist Party of China conceived of and asked for loyalty to the Party, reasons are given for their development, achievements, and failures.